Edukasi Pengobatan Tradisional Hipertensi Dengan Infusa Tanaman Obat Keluarga Pada Lansia di Puskesmas Pauh Padang - Rosiana Rizal; Helmice Afriyeni; Antonio . (LPPM Universitas Dharma Andalas, 2026)
Hypertension is a leading cause of premature death worldwide, some risk factors for hypertension are age, gender and obesity status. To reduce the risk of hypertension, hypertension treatment is needed as an effort to control hypertension, one of which is non-pharmacological treatment, usually carried out by implementing the use of family medicinal plants. The purpose of implementing Community Service activities at the Pauh Health Center is to increase public awareness, especially the elderly, about hypertension and hypertension treatment with traditional medicine. Using the method of providing education and question and answer discussions related to the dangers and efforts to prevent hypertension, the participants of this activity were carried out on December 2, 2025, at the Pauh Health Center Working Area. A total of 40 people. During the Education Process, the participants listened carefully and provided good feedback, in the form of benefits and how to consume infusa, and whether it can be boiled together with drinking water at home, and all questions from participants were answered well. With the question and answer from the participants, participants can better understand hypertension and how to treat it with traditional medicine.